THE ROLE OF THE PHILOSOPHY OF SCIENCE IN SUPPORTING HUMAN LIFE IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 AND SOCIETY 5.0 - Haidir Haidir; Sarda Nuria; Yanti Fitria; Yeni Erita (Jurnal Tunas Pendidikan, 2026)
Philosophy is the basis of human thinking in the world of education and provides a basis for thinking in the investigation and exploration of science. Philosophy and science are always developing to overcome existing problems. This research aims to determine the role of philosophy of science in supporting human life in the era of industrial revolution 4.0 and Society 5.0. Both act as a link between change and progress in the world of science and technology. Quantitative research methods through literature study. The development of science and technology is clear evidence of the problems faced by society today, or what is better known as the turmoil that accompanies major changes in various areas of social life. The role of philosophy and the development of science in human life is very influential, in completing work and industry has been replaced by science and technology such as artificial intelligence, robots and computers. This can be said to be the effect of the erosion of humanity that always affects human life, and the sophistication of technology.